Analisis pengaruh Influencer terhadap pembentukan harga saham di Bursa Efek Indonesia - I Gede Ananda Wibawa Putra; Luh Putu Mahyuni (FORUM EKONOMI, 2023)
This study aims to obtain empirical evidence regarding the influence of stock Influencers on the formation of stock prices on the Indonesia Stock Exchange (IDX). This research was carried out on publicly listed companies on the IDX and on stock Influencer Instagram social media accounts. The data is processed using an event study approach and takes into account abnormal returns. In addition, the Kolmogorov-Smirnov test and paired t-test were carried out. This study finds that buying sentiment and holding sentiment given by stock Influencers cannot have a significant influence on the formation of stock prices on the IDX. This is likely because investors have confidence and good financial literacy, so they are not too influenced by stock Influencers. But in market capitalization there is an influence from Influencers on large market capitalization. This may be because this research does not focus on the types of investors who invest in a market capitalization. This research study is implemented to be able to contribute information and decision making related to an active Influencer in the capital market world in providing a sentiment or recommendation.